Suggestion and Upgrading Extreme Programming Methodology in Web-Based Project Development - Gheni, A.Y. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research, we will discuss how to improve the work by dealing with the factors that participates in enhancing small IT organization to produce the software using the suitable development process supported by experimental theories to achieve the goals. Starting from the selecting of the methodology to implement the software. The steps used are and should be compatible with the type of the products the organization will produce and here it is the Web-Based Project Development. The researcher suggest Extreme Programming (XP) as a methodology for the Web-Based Project Development and justifying this suggestion and that will guide to know how the methodology is very important and effective in the software developments. Also the organization activities will be explained to put the software development process into the context and to know how much these activities are affective on the nature of the product that the organization intends to produce. The research focus on the limitation of pair programming style which is used in Extreme Programming methodology (XP) and suggest a solo programming style instead of pair programming style in that methodology. Also the research came up with guide can help the project manager to choose a solo programmer to be instead of pair programmers to improve the methodology in Web-Based Project Development.